Assessment of serological response of chickens to Salmonella Gallinarum and Salmonella Pullorum by Elisa - Oliveira, Gh De [UNESP]; Berchieri Júnior, Â [UNESP]; Montassier, Hj [UNESP]; Fernandes, Ac [UNESP] (Fundação APINCO de Ciência e Tecnologia Avícolas, 2004)
This study was done to assess an enzyme-linked immunosorbent assay (ELISA) to detect chicken serological response against Salmonella enterica serotypes Gallinarum and Pullorum. The assays have used soluble bacterial proteins of Salmonella Gallinarum strain 9 (AgSG) as detecting antigen and peroxidase and alkaline phosphatase conjugates. According to the results, the antigen, sera and conjugate concentrations were optimized. In addition, the assay using alkaline phosphatase and peroxidase conjugates was helpful to distinguish positive serological reaction to serotypes Gallinarum and Pullorum from Enteritidis.
Keywords: Chickens; conjugate; ELISA; Salmonella sp; serology